A giant leiomyoma of the breast (Indian Journal of Case Reports, 2021)
Breast leiomyoma is a rare benign tumor arising from the nipple and/or areola or from smooth muscle metaplasia of myoepithelial or myofibroblast cells. Despite its benign morphology, breast leiomyoma can create diagnostic confusion. Here, we report a rare case of a single leiomyoma of the breast in a 52-year-old woman. The patient reported a lump in her right breast for 1 year, and in the past 6 months, it has grown in size. Physical examination showed a dense mass in the right breast, without axillary lymphadenomegaly. Excisional biopsy revealed a well-defined cell tumor by intertwining the spindle cell folds with fibrillar and eosinophilic cytoplasm. Histopathological and immunohistochemical studies help to discriminate between leiomyoma and other benign and malignant breast lesions. Her results are discussed in our report.